1999
DOI: 10.1038/18230
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of the cyclin-dependent-kinase inhibitor p27Kip1 is instigated by Jab1

Abstract: The proliferation of mammalian cells is under strict control, and the cyclin-dependent-kinase inhibitory protein p27Kip1 is an essential participant in this regulation both in vitro and in vivo. Although mutations in p27Kip1 are rarely found in human tumours, reduced expression of the protein correlates well with poor survival among patients with breast or colorectal carcinomas, suggesting that disruption of the p27Kip1 regulatory mechanisms contributes to neoplasia. The abundance of p27Kip1 in the cell is det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

29
531
2
5

Year Published

1999
1999
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 581 publications
(567 citation statements)
references
References 30 publications
29
531
2
5
Order By: Relevance
“…12 Upon mitogenic stimulation, Jab1 causes p27 transfer to the cytoplasm and accelerates its degradation via the ubiquitin/proteasome pathway. 1,18,22 It has been shown that Jab1 has nuclear localization in proliferating cells, but cytoplasmic Jab1 increases as p27 relocates from nucleus to cytoplasm. 18,21 Recent studies revealed that Jab1 has both cytoplasmic and nuclear localization in undifferentiated tumors comparing with a predominantly nuclear localization in differentiated tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12 Upon mitogenic stimulation, Jab1 causes p27 transfer to the cytoplasm and accelerates its degradation via the ubiquitin/proteasome pathway. 1,18,22 It has been shown that Jab1 has nuclear localization in proliferating cells, but cytoplasmic Jab1 increases as p27 relocates from nucleus to cytoplasm. 18,21 Recent studies revealed that Jab1 has both cytoplasmic and nuclear localization in undifferentiated tumors comparing with a predominantly nuclear localization in differentiated tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…1,18,22 It has been shown that Jab1 has nuclear localization in proliferating cells, but cytoplasmic Jab1 increases as p27 relocates from nucleus to cytoplasm. 18,21 Recent studies revealed that Jab1 has both cytoplasmic and nuclear localization in undifferentiated tumors comparing with a predominantly nuclear localization in differentiated tumor cells. 24,39 Significantly, in our series, we identified Jab1 cytoplasmic expression in 11 out of 36 (29%) p27-negative primary and metastatic melanoma cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since p53 was mainly induced in the early phase, it is likely that p53 may have an important role in the initial phase that is when DNA were mainly damaged by bleomycin itself but not at a later stage when DNA are damaged mainly by infiltrating inflammatory cells.p21 is most probably playing an important role in the p53-induced G1 arrest because it is a potential inhibitor of cyclin-dependent kinase activity (Cheng et al, 1999;Haapajärvi et al, 1999;Rousseau et al, 1999;Sheikh et al, 1997;Tomoda et al, 1999;Wu et al, 1998a). It has been shown previously that serum or individual growth factors such as platelet-derived growth factor, fibroblast growth factor, and epidermal growth factor but not insulin are able to induce p21 in quiescent p53-deficient cells as well as normal cells (Michieli et al, 1994).…”
Section: Discussionmentioning
confidence: 99%